Adult mortality and consumption growth in the age of HIV/AIDS - Beegle, K; De Weerdt, J; Dercon, S (2007)
This paper uses a 13-year panel of individuals in Tanzania to assess how adult mortality shocks affect both short and long-run consumption growth of surviving household members. Using unique data which tracks individuals from 1991 to 2004, we examine consumption growth, controlling for a set of initial community, household and individual characteristics; the effect is identified using the sample of households in 2004 which grew out of baseline households. We find robust evidence that an affected household will see consumption drop 7 percent within the first five years after the adult death. With high growth in the sample over this time period, this creates a 19 percentage point growth gap with the average household. There is some evidence of persistent effects of these shocks for up to 13 years, but these effects are imprecisely estimated and not significantly different from zero. The impact of female adult death is found to be particularly severe.